Tissue-like natural collagen composite absorbable suture line and preparation method and application thereof

By using tissue-like natural collagen composite absorbable sutures, the problems of fast biodegradability and insufficient mechanical strength of traditional collagen products are solved, and collagen sutures with high mechanical properties, excellent biodegradability and low cost are achieved.

CN119564916AActive Publication Date: 2025-03-07FILLDERM (CHANGCHUN) MEDICINE BIOLOGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411675964.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing collagen-related products have relatively fast biodegradability and insufficient mechanical strength, making it difficult to meet the requirements of good flexibility, high strength and good biocompatibility.

Method used

The composite absorbable suture is made of tissue-like natural collagen, which includes medical grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles and sodium alginate, and is prepared by blending and spinning.

Benefits of technology

It improves the mechanical properties, biodegradability, antibacterial properties and descarriage properties of the material, has low antigenicity and low cost, and has excellent immobility and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564916A_ABST
    Figure CN119564916A_ABST
Patent Text Reader

Abstract

The invention provides a tissue-like natural collagen composite absorbable suture line as well as a preparation method and application thereof, and relates to a biomedical material. The invention provides a tissue-like natural collagen composite absorbable suture line. The tissue-like natural collagen composite absorbable suture line comprises medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles and sodium alginate. The tissue-like natural collagen composite absorbable suture line provided by the invention fully combines the advantages and functions of the used components, retains the excellent mechanical properties and biodegradability of the natural collagen composite material, is low in antigenicity and excellent in antibacterial property, also combines the photo-thermal effect of molybdenum disulfide, and has an obvious scar elimination effect; meanwhile, corrosion of bile, urine and pancreatic juice can be resisted, and cell growth is promoted; the reutilization of natural biological tissues is realized, and excellent use strength, antibacterial property and scar-removing property are achieved; the raw materials are wide in source and low in cost, and have great advantages in the field of medical suture materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a tissue-like natural collagen composite absorbable suture thread and a preparation method and application thereof. Background Art

[0002] Sutures refer to a special type of thread used in surgical manuscripts for wound ligation, hemostasis and tissue suture. According to the different biodegradability of the raw material components, they can be divided into two categories: non-absorbable sutures and absorbable sutures. The former usually does not degrade naturally in the human body, so the sutures need to be removed after suturing, which is easy to leave scars on the sutured epidermis; the components of the latter can be degraded into soluble products in the human body, which are generally absorbed and excreted by the human body within 2 to 6 months. Absorbable sutures include natural fibers (catgut, silk, collagen, chitin fibers, etc.) and synthetic polymer sutures. Under ideal conditions, absorbable sutures should meet the properties of good flexibility, high strength, good biocompatibility, easy storage, stable quality, and thorough disinfection and sterilization.

[0003] Collagen is the main component of mammalian skin, cartilage, ligaments and other tissues. It has good biocompatibility, degradable absorbability, no foreign body reaction, and low antigenicity. It can effectively promote cell growth and is used as a material for absorbable sutures. However, the current collagen-related products are basically materials at the collagen molecule level with a triple helix structure, which have obvious advantages in tissue compatibility, inducing tissue regeneration and other properties. However, the collagen tissue in traditional collagen products is prepared by degradation, which destroys the aggregated structural morphology of natural collagen itself, resulting in relatively fast biodegradability and insufficient mechanical strength. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a tissue-like natural collagen composite absorbable suture and its preparation method and application. The tissue-like natural collagen composite absorbable suture provided by the present invention has excellent mechanical properties, biodegradability, antibacterial properties and scar removal, low antigenicity and low cost, and also has good fixation.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a tissue-like natural collagen composite absorbable suture thread, which comprises medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles and sodium alginate.

[0007] Preferably, the mass ratio of the tissue-like natural collagen to the epoxidized modified chitosan is 10:0.25-1.5;

[0008] The mass ratio of the medical-grade tissue-like natural collagen to the molybdenum dioxide nanoparticles is 10:0.01-0.1;

[0009] The mass ratio of the medical-grade tissue-like natural collagen to sodium alginate is 10:0.25-1.5;

[0010] The molybdenum dioxide nanoparticles include monoclinic molybdenum dioxide nanoparticles.

[0011] Preferably, the method for preparing the medical-grade tissue-like natural collagen comprises the following steps:

[0012] (1) removing subcutaneous tissue of animal skin and soaking in physiological saline to obtain pretreated animal skin;

[0013] (2) degreasing the pretreated animal hide to obtain a defatted animal hide;

[0014] (3) dehairing the defatted animal hide to obtain a dehaired animal hide;

[0015] (4) subjecting the depilated animal skin to a deswelling treatment to obtain a deswelling animal skin;

[0016] (5) subjecting the de-swollen animal skin to an acid swelling treatment to obtain an acid swollen animal skin;

[0017] (6) The acid-swollen animal skin is crushed, the pH value is adjusted to 7-7.4, the solid-liquid separation is performed to obtain a solid component, and the solid component is washed with water and then dried to obtain medical-grade tissue-like natural collagen.

[0018] Preferably, in step (2), the degreasing treatment comprises: adding a degreasing agent and water to the pretreated animal skin to perform a degreasing treatment;

[0019] The mass ratio of the pretreated animal skin to the degreasing agent is 1:0.01-0.04;

[0020] The degreasing agent includes one or more of alkyl polyglycosides, peregrin, washing powder, sodium lauryl sulfate and fatty alcohol polyoxyethylene ether;

[0021] The mass volume ratio of the pretreated animal skin to water is 1kg:1.5-3L;

[0022] The degreasing treatment is performed at a temperature of 30 to 37°C for 2 to 5 hours;

[0023] The degreasing treatment further includes water washing;

[0024] In step (3), the depilatory treatment includes: adding the defatted animal skin, water, polyoxyethylene ether and ferrous salt to perform a first depilatory treatment, adding alcohol amine to perform a second depilatory treatment, adding an alkaline agent to perform a third depilatory treatment, adding an oxidant to perform a fourth depilatory treatment, and adding a dilute alkaline agent aqueous solution to perform a fifth depilatory treatment;

[0025] The mass volume ratio of the defatted animal skin and water is 1kg:1-2L;

[0026] The polyoxyethylene ether includes fatty alcohol polyoxyethylene ether and / or nonylphenol polyoxyethylene ether; the mass ratio of the pretreated animal skin to the polyoxyethylene ether is 1:0.3-0.6;

[0027] The ferrous salt includes ferrous sulfate and / or ammonium ferrous sulfate; the mass ratio of the pretreated animal skin to the ferrous salt is 1:0.3-0.6;

[0028] The first hair removal treatment lasts for 90 to 150 minutes;

[0029] The alcoholamine includes one or more of triethanolamine, monoethanolamine and diethanolamine; the mass ratio of the pretreated animal skin to the alcoholamine is 1:0.01-0.03;

[0030] The second hair removal treatment lasts for 10 to 20 minutes;

[0031] The alkaline reagent includes alkali metal hydroxide and / or alkali metal carbonate; the mass ratio of the pretreated animal skin to the alkaline reagent is 1:0.035-0.045;

[0032] The third hair removal treatment lasts for 15 to 25 minutes;

[0033] The oxidant includes one or more of hydrogen peroxide, sodium perborate and sodium percarbonate; the mass ratio of the pretreated animal skin to the oxidant is 1:0.06-0.08;

[0034] The fourth hair removal treatment lasts for 3 to 4 hours;

[0035] The alkaline agent in the dilute alkaline agent aqueous solution includes alkali metal hydroxide and / or alkali metal carbonate; the mass fraction of the dilute alkaline agent aqueous solution is 0.3-0.8%; the time of the fifth depilatory treatment is 4-6 hours;

[0036] The depilatory treatment also includes washing with water;

[0037] In step (4), the deswelling treatment comprises: adding a first portion of water and an inorganic salt to the dehaired animal skin for a first deswelling treatment, adding a second portion of water, adjusting the pH value to 4 to 4.5, adding acid lipase for a second deswelling treatment, and adding acid protease for a third deswelling treatment;

[0038] The mass volume ratio of the pretreated animal skin to the first part of water is 1kg:0.8-1L;

[0039] The inorganic salt includes one or more of sodium bisulfite, ammonium sulfate, ammonium chloride and ammonium acetate; the mass of the inorganic salt accounts for 0.05-0.2% of the mass of the pretreated animal skin;

[0040] The temperature of the first deswelling treatment is 28-35°C, the time is 50-60 minutes, and the end point pH value is 8-8.5;

[0041] The mass volume ratio of the pretreated animal skin to the second part of water is 1 kg: 1 to 4 L;

[0042] The mass of the acid lipase accounts for 0.1-0.3% of the mass of the pretreated animal skin; the enzyme activity of the acid lipase is 50,000-60,000 units / g;

[0043] The second deswelling treatment is performed at a temperature of 28 to 35°C for 15 to 20 minutes;

[0044] The mass of the acidic protease accounts for 0.1-0.3% of the mass of the pretreated animal skin; the enzyme activity of the acidic protease is 80,000-100,000 units / g;

[0045] The temperature of the third deswelling treatment is 38-42°C and the time is 2-5 hours;

[0046] The deswelling treatment further includes washing with water;

[0047] In step (5), the acid swelling treatment comprises: adding water to the de-swollen animal skin, adjusting the pH value to 2.8 to 3.0, stirring the acid swelling treatment and then standing the acid swelling treatment;

[0048] The mass volume ratio of the pretreated animal skin to water is 1 kg: 1 to 2 L;

[0049] The stirring acid swelling treatment time is 30 to 60 minutes;

[0050] The time of the static acid swelling treatment is 6 to 8 hours;

[0051] The acid swelling treatment further includes water washing.

[0052] In step (6), the pulverization includes ball milling, the ball-to-material ratio of the ball milling is 1:1-5, the rotation speed is 200-600 r / min, and the time is 1-3 h;

[0053] The drying comprises freeze drying;

[0054] The drying process also includes disinfection and sterilization.

[0055] Preferably, the epoxidized modified chitosan comprises epoxidized modified chitosan obtained by epoxidizing chitosan with ethylene glycol diglycidyl ether.

[0056] Preferably, the preparation method of the epoxidized modified chitosan comprises the following steps:

[0057] Chitosan, ethylene glycol diglycidyl ether and water are mixed and epoxidized to obtain epoxidized modified chitosan.

[0058] The present invention also provides a method for preparing the tissue-like natural collagen composite absorbable suture described in the above technical solution, comprising the following steps:

[0059] Medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles, sodium alginate and water are mixed to obtain a spinning solution;

[0060] The spinning solution is spun to obtain a tissue-like natural collagen composite absorbable suture thread.

[0061] Preferably, the mass ratio of the tissue-like natural collagen to the epoxidized modified chitosan is 10:0.25-1.5;

[0062] The mass ratio of the medical-grade tissue-like natural collagen to the molybdenum dioxide nanoparticles is 10:0.01-0.1;

[0063] The mass ratio of the medical-grade tissue-like natural collagen to sodium alginate is 10:0.25-1.5;

[0064] The concentration of medical grade natural collagen in the spinning solution is 12-25wt%.

[0065] Preferably, the spinning process conditions include: the coagulation bath is saturated sodium sulfate; the pressure is 0.05-0.2 MPa; the spinning solution temperature is room temperature; the coagulation temperature is 25-35° C.; and the winding speed is 8-15 m / min.

[0066] The present invention also provides the use of the tissue-like natural collagen composite absorbable suture thread described in the above technical solution or the tissue-like natural collagen composite absorbable suture thread prepared by the preparation method described in the above technical solution in tissue engineering, regenerative medicine materials or implantable medical devices.

[0067] The medical-grade tissue-like natural collagen used in the present invention has good biocompatibility, suitable biodegradability, good mechanical properties, excellent thermal stability and structural stability, low antigenicity and easy preservation, and can quickly and effectively stop bleeding, promote wound healing and repair, and is an ideal material for biomedical materials. It can fundamentally and thoroughly solve the problems of fast biodegradation and insufficient mechanical strength of collagen molecular-level materials or gelatin materials. The present invention supplements and modifies the material by adding epoxidized modified chitosan, which has an inhibitory effect on the growth of various bacteria and fungi, and can also promote skin regeneration and accelerate wound healing after suture.

[0068] Molybdenum dioxide is a metallic semiconductor with good electrical conductivity. The present invention can not only improve the conductivity of the tissue-like natural collagen composite absorbable suture thread by adding molybdenum dioxide nanoparticles, but also further enhance its wear resistance and anti-slip properties. In addition, the photothermal effect of molybdenum disulfide can also bring about obvious scar elimination effect.

[0069] The sodium alginate added in the present invention is a linear polysaccharide, which has the characteristics of excellent biocompatibility, biodegradability, non-toxicity and low raw material cost. Chitosan and its derivatives have a broad spectrum of antibacterial effects, can inhibit the reproduction and growth of various bacteria and fungi, and have the advantages of non-toxicity and strong antibacterial properties. Wound dressings added with chitosan can prevent bacterial penetration, promote skin regeneration, and accelerate wound healing, coupled with its good biocompatibility, strength, flexibility and bioabsorbability.

[0070] The natural collagen composite absorbable suture provided by the present invention is composed of collagen, chitosan, molybdenum dioxide nanoparticles and sodium alginate, which has a wider source, low cost, and realizes the efficient use of natural biomaterials. The tissue-like natural collagen composite absorbable suture fully combines the advantageous functions of each component, retains the excellent mechanical properties and biodegradability of natural collagen composite materials, has low antigenicity and excellent antibacterial properties; it also combines the photothermal effect of molybdenum disulfide, and has an obvious scar elimination effect; it also has good fixation, and can also resist the corrosion of bile, urine and pancreatic juice, and promote cell growth; the adsorption bonds formed between different components not only further ensure the strength of the natural collagen composite absorbable suture, but also give it the advantages of antibacterial and scar removal.

[0071] The preparation method of the natural collagen composite absorbable suture provided by the present invention has the characteristics of wide source of raw materials, simple process, low production cost, short production cycle, and green and environmentally friendly preparation process. The tissue-like natural collagen composite absorbable suture prepared by the method has excellent mechanical properties and biodegradability, low antigenicity and low cost, and also has good fixation. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 1;

[0073] Figure 2 This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 2;

[0074] Figure 3 This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 3;

[0075] Figure 4 The MTT test results of collagen, antigen-free collagen aggregates prepared in Comparative Example 1, and medical-grade tissue-like natural collagen prepared in Example 4;

[0076] Figure 5 This is the result of 24h scratching of collagen;

[0077] Figure 6 This is a 24h scratch result diagram of the antigen-free collagen aggregate prepared in Comparative Example 1;

[0078] Figure 7 This is a graph showing the 24h scratch results of the medical-grade tissue-like natural collagen prepared in Example 4. DETAILED DESCRIPTION

[0079] The invention provides a tissue-like natural collagen composite absorbable suture thread, which comprises medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles and sodium alginate.

[0080] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0081] In the present invention, the mass ratio of the tissue-like natural collagen to the epoxidized modified chitosan is preferably 10:0.25-1.5, and in specific embodiments, it can be 10:0.25, 10:0.5, 10:0.75, 10:1, 10:1.25 or 10:1.5. In the present invention, the epoxidized modified chitosan preferably includes epoxidized modified chitosan obtained by epoxidizing chitosan with ethylene glycol diglycidyl ether, and the epoxidized modified chitosan preferably has a structure shown in Formula I, wherein n in Formula I is 2-10, and in specific embodiments, it can be 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0082]

[0083] In the present invention, the tissue-like natural collagen has good biocompatibility, suitable biodegradability, good mechanical properties, excellent thermal stability and structural stability, low antigenicity and easy preservation, and can quickly and effectively stop bleeding, promote wound healing and repair, and is an ideal material for biomedical materials. The tissue-like natural collagen used in the present invention as a raw material can fundamentally and thoroughly solve the problems of insufficient biodegradability, mechanical strength and other properties of collagen molecular hierarchical materials or gelatin materials.

[0084] The present invention uses epoxidized modified chitosan to supplement and modify the tissue-like natural collagen composite absorbable suture thread, and the enhanced composite fiber has an inhibitory effect on the growth of various bacteria and fungi, can also promote skin regeneration, and accelerate wound healing after suture.

[0085] In the present invention, the mass ratio of the medical-grade tissue-like natural collagen to the molybdenum dioxide nanoparticles is preferably 10:0.01-0.1, and in specific embodiments, it can be 10:0.01, 10:0.02, 10:0.03, 10:0.04, 10:0.05, 10:0.06, 10:0.07, 10:0.08, 10:0.09 or 10:0.1. In the present invention, the molybdenum dioxide nanoparticles include monoclinic molybdenum dioxide nanoparticles. Molybdenum dioxide, as a metallic semiconductor, has good electrical conductivity. The present invention can not only improve the conductivity of the suture by adding molybdenum dioxide nanoparticles, but also further improve the wear resistance and anti-slip properties of the spun fiber, and the photothermal effect of molybdenum disulfide can also bring about obvious scar elimination effect.

[0086] In the present invention, the mass ratio of the medical-grade tissue-like natural collagen to sodium alginate is preferably 10:0.25-1.5, and in specific embodiments, it can be 10:0.25, 10:0.5, 10:0.75, 10:1, 10:1.25 or 10:1.5. The sodium alginate added in the present invention is a linear polysaccharide, which has the characteristics of excellent biocompatibility, biodegradability, non-toxicity and low raw material cost, and is widely used in the fields of medicine, health, food and cosmetics.

[0087] In the present invention, the cross section of the tissue-like natural collagen composite absorbable suture is preferably circular. The tissue-like natural collagen composite absorbable suture provided by the present invention fully combines the advantageous functions of the components used, retains the excellent mechanical properties and biodegradability of natural collagen composite materials, has low antigenicity and excellent antibacterial properties; it also combines the photothermal effect of molybdenum disulfide, and has an obvious scar elimination effect; it also has good fixation, and can also resist the corrosion of bile, urine and pancreatic juice, and promote cell growth.

[0088] The preparation method of medical-grade tissue-like natural collagen is described in detail below.

[0089] In the present invention, the method for preparing the medical-grade tissue-like natural collagen comprises the following steps:

[0090] (1) removing subcutaneous tissue of animal skin and soaking in physiological saline to obtain pretreated animal skin;

[0091] (2) degreasing the pretreated animal hide to obtain a defatted animal hide;

[0092] (3) dehairing the defatted animal hide to obtain a dehaired animal hide;

[0093] (4) subjecting the depilated animal skin to a deswelling treatment to obtain a deswelling animal skin;

[0094] (5) subjecting the de-swollen animal skin to an acid swelling treatment to obtain an acid swollen animal skin;

[0095] (6) The acid-swollen animal skin is crushed, the pH value is adjusted to 7-7.4, the solid-liquid separation is performed to obtain a solid component, and the solid component is washed with water and then dried to obtain medical-grade tissue-like natural collagen.

[0096] The invention removes subcutaneous tissue of animal skin and soaks it in physiological saline to obtain pretreated animal skin.

[0097] In the present invention, the animal skin preferably includes one or more animal skins of pigs, cattle and sheep; the animal skin is preferably fresh and traceable animal skin.

[0098] The present invention preferably first cleans the animal skin, soaks it in water, and then removes the subcutaneous tissue of the animal skin. In the present invention, the purpose of the cleaning is to remove dirt on the animal skin. In the present invention, the temperature of the water soaking is preferably room temperature, and the time of the water soaking is preferably 60 to 120 minutes, and in specific embodiments it can be 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes. In the present invention, the method of removing the subcutaneous tissue of the animal skin preferably includes mechanical meat cutting; the subcutaneous tissue includes subcutaneous fat, surface muscle, blood vessels and fascia tissue.

[0099] In the present invention, the animal skin with subcutaneous tissue removed is preferably cut into pieces, washed with saline, and then soaked in saline. In the present invention, the size of the animal pieces obtained by cutting is preferably 5-10 mm×5-10 mm. In the present invention, the temperature of the saline soaking is preferably room temperature, and the time of the saline soaking is preferably 10-18 hours, and in specific embodiments, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours or 18 hours.

[0100] After obtaining the pretreated animal skin, the present invention performs a degreasing treatment on the pretreated animal skin to obtain the defatted animal skin.

[0101] In the present invention, the degreasing treatment preferably comprises: adding a degreasing agent and water to the pretreated animal skin to perform degreasing treatment;

[0102] In the present invention, the mass volume ratio of the pretreated animal skin to water is preferably 1kg:1.5-3L. In specific embodiments, it can be 1kg:1.5L, 1kg:1.6L, 1kg:1.7L, 1kg:1.8L, 1kg:1.9L, 1kg:2L, 1kg:2.1L, 1kg:2.2L, 1kg:2.3L, 1kg:2.4L, 1kg:2.5L, 1kg:2.6L, 1kg:2.7L, 1kg:2.8L, 1kg:2.9L or 1kg:3L.

[0103] In the present invention, the degreasing agent preferably includes one or more of alkyl polyglycosides, peregal, washing powder, sodium lauryl sulfate and fatty alcohol polyoxyethylene ether. In the present invention, the mass ratio of the pretreated animal skin to the degreasing agent is preferably 1:0.01-0.04, and in specific embodiments, it can be 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035 or 1:0.04.

[0104] In the present invention, the temperature of the degreasing treatment is preferably 30-37°C, and in specific embodiments it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C or 37°C; the time of the degreasing treatment is preferably 2-5h, and in specific embodiments it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h; the degreasing treatment is preferably carried out in a rotating drum; the rotation speed of the rotating drum is preferably 5-12r / min, and in specific embodiments it can be 5r / min, 6r / min, 7r / min, 8r / min, 9r / min, 10r / min, 11r / min or 12r / min.

[0105] In the present invention, the degreasing treatment preferably further comprises: washing the animal skin after the degreasing treatment to obtain defatted animal skin. In the present invention, the number of times of the water washing is preferably 3 to 5 times, more preferably 4 times; the temperature of the water used for the water washing is preferably the same as the temperature of the degreasing treatment.

[0106] After obtaining the defatted animal skin, the present invention performs a dehairing treatment on the defatted animal skin to obtain the dehaired animal skin.

[0107] In the present invention, the dehairing treatment preferably includes: adding the defatted animal skin, water, polyoxyethylene ether and ferrous salt for the first dehairing treatment, adding alcohol amine for the second dehairing treatment, adding alkaline reagent for the third dehairing treatment, adding oxidant for the fourth dehairing treatment, and adding dilute alkaline reagent aqueous solution for the fifth dehairing treatment. In the present invention, the temperature of the dehairing treatment is preferably room temperature, and the dehairing treatment is preferably carried out in a rotary drum; the rotation speed of the rotary drum is preferably 5 to 12 r / min, and in specific embodiments it can be 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min, 10 r / min, 11 r / min or 12 r / min.

[0108] In the present invention, the mass ratio of the defatted animal skin and water is preferably 1kg:1-2L. In specific embodiments, it can be 1kg:1L, 1kg:1.1L, 1kg:1.2L, 1kg:1.3L, 1kg:1.4L, 1kg:1.5L, 1kg:1.6L, 1kg:1.7L, 1kg:1.8L, 1kg:1.9L or 1kg:2L.

[0109] In the present invention, the polyoxyethylene ether preferably includes fatty alcohol polyoxyethylene ether and / or nonylphenol polyoxyethylene ether. In the present invention, the mass ratio of the pretreated animal skin to the polyoxyethylene ether is preferably 1:0.3-0.6, and in specific embodiments it can be 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55 or 1:0.6.

[0110] In the present invention, the ferrous salt preferably includes ferrous sulfate and / or ammonium ferrous sulfate. In the present invention, the mass ratio of the pretreated animal skin to the ferrous salt is preferably 1:0.3-0.6, and in specific embodiments it can be 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55 or 1:0.6.

[0111] In the present invention, the time of the first hair removal treatment is preferably 90 to 150 minutes, and in specific embodiments may be 90 minutes, 100 minutes, 110 minutes, 120 minutes, 130 minutes, 140 minutes or 150 minutes.

[0112] In the present invention, the alcoholamine preferably includes one or more of triethanolamine, monoethanolamine and diethanolamine. In the present invention, the mass ratio of the pretreated animal skin to the alcoholamine is preferably 1:0.01-0.03, and in specific embodiments it can be 1:0.01, 1:0.015, 1:0.02, 1:0.025 or 1:0.03.

[0113] In the present invention, the time of the second hair removal treatment is preferably 10 to 20 minutes, and in specific embodiments it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes.

[0114] In the present invention, the alkaline agent preferably includes alkali metal hydroxide and / or alkali metal carbonate; the alkali metal hydroxide preferably includes sodium hydroxide and / or potassium hydroxide; the alkali metal carbonate preferably includes sodium carbonate and / or potassium carbonate. In the present invention, the mass ratio of the pretreated animal skin to the alkaline agent is preferably 1:0.035-0.045, and in specific embodiments it can be 1:0.035, 1:0.036, 1:0.037, 1:0.038, 1:0.039, 1:0.04, 1:0.041, 1:0.042, 1:0.043, 1:0.044 or 1:0.045.

[0115] In the present invention, the time of the third hair removal treatment is preferably 15 to 25 minutes, and in specific embodiments it can be 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes or 25 minutes.

[0116] In the present invention, the oxidant preferably includes one or more of hydrogen peroxide, sodium perborate and sodium percarbonate; the mass concentration of the hydrogen peroxide is preferably 1-30%, and in specific embodiments it can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 10%, 15%, 20%, 25% or 30%. In the present invention, the mass ratio of the pretreated animal skin to the oxidant is preferably 1:0.06-0.08, and in specific embodiments it can be 1:0.061, 1:0.062, 1:0.063, 1:0.064, 1:0.065, 1:0.066, 1:0.067, 1:0.068, 1:0.069, 1:0.07, 1:0.071, 1:0.072, 1:0.073, 1:0.074, 1:0.075, 1:0.076, 1:0.077, 1:0.078, 1:0.079 or 1:0.08.

[0117] In the present invention, the duration of the fourth hair removal treatment is preferably 3 to 4 hours, and in specific embodiments may be 180 minutes, 190 minutes, 200 minutes, 210 minutes, 220 minutes, 230 minutes or 240 minutes.

[0118] In the present invention, the mass fraction of the dilute alkaline reagent aqueous solution is preferably 0.3-0.8%, and in specific embodiments it can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%; in the present invention, the alkaline reagent in the dilute alkaline reagent aqueous solution preferably includes alkali metal hydroxide and / or alkali metal carbonate. The alkali metal hydroxide preferably includes sodium hydroxide and / or potassium hydroxide; the alkali metal carbonate preferably includes sodium carbonate and / or potassium carbonate. The present invention has no special limitation on the amount of the dilute alkaline reagent aqueous solution, and it only needs to be able to immerse the animal skin after the fourth depilation treatment.

[0119] In the present invention, the fifth hair removal treatment is preferably performed for 4 to 6 hours, and in specific embodiments may be 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0120] In the present invention, the depilatory treatment preferably further comprises: washing the depilated animal skin with water to obtain the depilated animal skin. In the present invention, the number of times of washing with water is preferably 3 to 5 times, more preferably 4 times.

[0121] After obtaining the depilated animal skin, the present invention performs a deswelling treatment on the depilated animal skin to obtain the deswelling animal skin.

[0122] In the present invention, the deswelling treatment preferably includes: adding a first part of water and an inorganic salt to the dehaired animal skin for a first deswelling treatment, adding a second part of water, adjusting the pH value to 4-4.5, adding acid lipase for a second deswelling treatment, and adding acid protease for a third deswelling treatment; the deswelling treatment is preferably carried out in a rotating drum; the rotation speed of the rotating drum is preferably 5-10 r / min, and in specific embodiments it can be 5r / min, 6r / min, 7r / min, 8r / min, 9r / min or 10r / min.

[0123] In the present invention, the mass volume ratio of the pretreated animal skin to the first part of water is preferably 1kg:0.8-1L, and in specific embodiments it can be 1kg:0.8L, 1kg:0.85L, 1kg:0.9L, 1kg:0.95L or 1kg:1L.

[0124] In the present invention, the inorganic salt preferably includes one or more of sodium bisulfite, ammonium sulfate, ammonium chloride and ammonium acetate; the mass of the inorganic salt preferably accounts for 0.05-0.2% of the mass of the pretreated animal skin, and in specific embodiments it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.2%.

[0125] In the present invention, the temperature of the first deswelling treatment is preferably 28-35°C, and in specific embodiments it can be 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C; the time of the first deswelling treatment is preferably 50-60min, and in specific embodiments it can be 50min, 51min, 52min, 53min, 54min, 55min, 56min, 57min, 58min, 59min or 60min; the endpoint pH value of the first deswelling treatment is preferably 8-8.5, and in specific embodiments the endpoint pH value can be 8, 8.1, 8.2, 8.3, 8.4 or 8.5.

[0126] In the present invention, the mass volume ratio of the pretreated animal skin to the second part of water is preferably 1kg:1-4L. In specific embodiments, it can be 1kg:1L, 1kg:1.1L, 1kg:1.2L, 1kg:1.5L, 1kg:2L, 1kg:2.5L, 1kg:3L, 1kg:3.5L or 1kg:4L.

[0127] In the present invention, the mass of the acid lipase preferably accounts for 0.1-0.3% of the mass of the pretreated animal skin, and in specific embodiments it can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, .27%, 0.28%, 0.29% or 0.3%; the enzyme activity of the acid lipase is preferably 50,000 to 60,000 units / g, and in specific embodiments may be 50,000 units / g, 51,000 units / g, 50,000 units / g, 53,000 units / g, 54,000 units / g, 55,000 units / g, 56,000 units / g, 57,000 units / g, 58,000 units / g, 59,000 units / g or 60,000 units / g;

[0128] In the present invention, the temperature of the second deswelling treatment is preferably 28-35°C, and in specific embodiments it can be 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C; the time of the second deswelling treatment is preferably 15-20 min, and in specific embodiments it can be 15 min, 16 min, 17 min, 18 min, 19 min or 20 min.

[0129] In the present invention, the mass of the acidic protease accounts for 0.1-0.3% of the mass of the pretreated animal skin, and in specific embodiments it can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29% or 0.3%; the enzyme activity of the acidic protease is preferably 80,000-100,000 units / g. In specific embodiments, the amount of the present invention may be 80,000 units / g, 81,000 units / g, 82,000 units / g, 83,000 units / g, 84,000 units / g, 85,000 units / g, 86,000 units / g, 87,000 units / g, 88,000 units / g, 89,000 units / g, 90,000 units / g, 91,000 units / g, 92,000 units / g, 93,000 units / g, 94,000 units / g, 95,000 units / g, 96,000 units / g, 97,000 units / g, 98,000 units / g, 99,000 units / g or 100,000 units / g.

[0130] In the present invention, the temperature of the third deswelling treatment is preferably 38-42°C, and in specific embodiments it can be 38°C, 39°C, 40°C, 41°C or 42°C; the time of the third deswelling treatment is preferably 2-5h, and in specific embodiments it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h.

[0131] In the present invention, the deswelling treatment preferably further comprises: washing the deswelling treated animal skin with water to obtain the deswelling animal skin. In the present invention, the number of times of washing with water is preferably 3 to 5 times, more preferably 4 times.

[0132] After obtaining the de-swelling animal skin, the present invention performs acid swelling treatment on the de-swelling animal skin to obtain the acid-swollen animal skin.

[0133] In the present invention, the acid swelling treatment preferably includes: adding water to the de-swollen animal skin, adjusting the pH value to 2.8-3.0, stirring the acid swelling treatment and then allowing the acid swelling treatment to stand; the temperature of the acid swelling treatment is preferably room temperature, and the acid swelling treatment is preferably carried out in a rotating drum; the rotation speed of the rotating drum is preferably 5-12r / min, and in specific embodiments it can be 5r / min, 6r / min, 7r / min, 8r / min, 9r / min, 10r / min, 11r / min or 12r / min.

[0134] In the present invention, the mass volume ratio of the pretreated animal skin to water is preferably 1kg:1-2L. In specific embodiments, it can be 1kg:1L, 1kg:1.1L, 1kg:1.2L, 1kg:1.3L, 1kg:1.4L, 1kg:1.5L, 1kg:1.6L, 1kg:1.7L, 1kg:1.8L, 1kg:1.9L or 1kg:2L.

[0135] In the present invention, the acid used to adjust the pH value to 2.8-3.0 preferably includes formic acid solution and / or sulfuric acid solution; the mass concentration of the formic acid solution is preferably 0.05-0.08%, and in a specific embodiment it can be 0.05%, 0.06%, 0.07% or 0.08%; the mass concentration of the sulfuric acid solution is preferably 0.08-0.12%, and in a specific embodiment it can be 0.08%, 0.09%, 0.010%, 0.011% or 0.012%; when the acid is a mixed acid solution of formic acid solution and sulfuric acid solution, the volume ratio of formic acid solution to sulfuric acid solution in the mixed acid solution is preferably 1:2-3, more preferably 1:2.5.

[0136] In the present invention, the stirring acid swelling treatment time is preferably 30 to 60 minutes, and in specific embodiments it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.

[0137] In the present invention, the static acid swelling treatment time is preferably 6 to 8 hours, and in specific embodiments can be 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.

[0138] In the present invention, the acid swelling treatment preferably further comprises: washing the animal skin after the acid swelling treatment to obtain the acid swollen animal skin. In the present invention, the water washing is preferably performed 3 to 5 times, more preferably 4 times.

[0139] After obtaining the acid-swollen animal skin, the present invention crushes the acid-swollen animal skin, adjusts the pH value to 7-7.4, separates the solid and liquid to obtain a solid component, washes the solid component with water and then dries it to obtain medical-grade tissue-like natural collagen.

[0140] In the present invention, the pulverization preferably includes ball milling. In the present invention, the ball-to-material ratio of the ball milling is preferably 1:1-5, and in specific embodiments, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5; the rotation speed of the ball milling is preferably 200-600 r / min, and in specific embodiments, it can be 200 r / min, 300 r / min, 400 r / min, 500 r / min or 600 r / min; the time of the ball milling is preferably 1-3 hours, and in specific embodiments, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours. In the present invention, the grinding bodies used in the ball mill preferably include large balls and small balls; the particle size of the large balls is preferably 12-13 mm; the particle size of the small balls is preferably 9-10 mm; the number ratio of the large balls to the small balls is preferably 1:1-3, and in specific embodiments it can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.

[0141] After the ball milling, the present invention preferably further comprises centrifuging the ball milling system, removing the supernatant, collecting the slurry, and then adjusting the pH value of the slurry to 7 to 7.4. In the present invention, the rotation speed of the centrifugal separation is preferably 15000 to 18000 r / min, and in specific embodiments, it can be 15000 r / min, 16000 r / min, 17000 r / min or 18000 r / min; the time of the centrifugal separation is preferably 10 to 15 minutes, and in specific embodiments, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes.

[0142] In the present invention, the base used to adjust the pH value to 7-7.4 preferably includes one or more of hydroxides, carbonates and bicarbonates, and the hydroxide preferably includes one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide; the carbonate preferably includes sodium carbonate and / or potassium carbonate; the alkali metal bicarbonate preferably includes one or more of sodium bicarbonate, potassium bicarbonate and calcium bicarbonate; in a specific embodiment, the pH value can be 7, 7.1, 7.2, 7.3 or 7.4.

[0143] In the present invention, the solid-liquid separation preferably includes centrifugal separation, and the rotation speed of the centrifugal separation is preferably 15000-18000 r / min, and in specific embodiments it can be 15000 r / min, 16000 r / min, 17000 r / min or 18000 r / min; the time of the centrifugal separation is preferably 10-15 min, and in specific embodiments it can be 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.

[0144] In the present invention, the drying preferably includes freeze drying. The present invention has no particular limitation on the conditions of freeze drying, and freeze drying is sufficient.

[0145] In the present invention, after drying, the method further preferably includes: sterilizing the dried natural collagen to obtain medical-grade tissue-like natural collagen. In the present invention, the sterilization is preferably γ-ray sterilization; the dose of the γ-ray is preferably 6 to 25 KGy / h60Co, and in specific embodiments, it can be 6 KGy / h60Co, 7 KGy / h60Co, 8 KGy / h60Co, 9 KGy / h60Co, 10 KGy / h60Co, 11 KGy / h60Co, 12 KGy / h60Co, 3 KGy / h60 Co、14KGy / h60Co、15KGy / h60Co、16KGy / h60Co、17KGy / h60Co、18KGy / h60Co、19KGy / h60C o, 20KGy / h60Co, 21KGy / h60Co, 22KGy / h60Co, 23KGy / h60Co, 24KGy / h60Co or 25KGy / h60Co.

[0146] The present invention provides a method for preparing medical-grade tissue-like natural collagen, which has a simple process, simple equipment, abundant raw materials, low cost, and easy large-scale industrial production. The medical-grade tissue-like natural collagen prepared by the present invention has not undergone any degradation process of natural collagen, and its basic composition is the existence form of natural collagen in the tissue-collagen fiber bundles, and also has the spatial structural characteristics of natural collagen in the tissue, so that it can mimic the natural tissue structure to a greater extent. The medical-grade tissue-like natural collagen prepared by the present invention has more excellent mechanical properties and excellent enzyme resistance / thermal stability and structural stability, low antigenicity and easier to preserve, excellent hemostatic performance, and its high strength and toughness can meet the body's diversified requirements for material properties, and is an ideal collagen biomedical material. The medical-grade tissue-like natural collagen prepared by the present invention is conducive to cell survival, proliferation and differentiation, and can significantly promote tissue regeneration and repair in wound and scar repair, and reduce the generation of scars.

[0147] The preparation method of epoxidized modified chitosan is described in detail below.

[0148] In the present invention, the preparation method of the epoxidized modified chitosan comprises the following steps: mixing chitosan, ethylene glycol diglycidyl ether and water, and performing epoxidation modification to obtain epoxidized modified chitosan. The reaction scheme is as follows:

[0149]

[0150] In the present invention, the mixing preferably comprises: suspending chitosan in water, heating, and adding dropwise an aqueous solution of ethylene glycol diglycidyl ether.

[0151] In the present invention, the chitosan is preferably used in the form of chitosan powder. In the present invention, the mass volume ratio of the chitosan to water is preferably 2g:20-25mL, and in specific embodiments, it can be 2g:20mL, 2g:21mL, 2g:22mL, 2g:23mL, 2g:24mL or 2g:25mL.

[0152] In the present invention, the temperature after heating is preferably 95-100°C, and in specific embodiments can be 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.

[0153] In the present invention, the mass ratio of chitosan to ethylene glycol diglycidyl ether aqueous solution is preferably 2:0.5-5, and in specific embodiments, it can be 2:0.5, 2:1, 2:1.5, 2:2, 2:2.5, 2:3, 2:3.5, 2:4, 2:4.5 or 2:5. In the present invention, the mass concentration of ethylene glycol diglycidyl ether aqueous solution is preferably 1-5%, and in specific embodiments, it can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. The present invention has no special limitation on the dripping speed of the ethylene glycol diglycidyl ether aqueous solution, and it can be added dropwise at a uniform speed.

[0154] In the present invention, the temperature of the epoxidation modification is preferably 95-100°C, and in specific embodiments it can be 95°C, 96°C, 97°C, 98°C, 99°C or 100°C; the time of the epoxidation modification is preferably 2-6h, and in specific embodiments it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.

[0155] After the epoxidation modification is completed, the present invention preferably further comprises: filtering the reaction system obtained by the epoxidation modification, washing the obtained solid with water, washing with ethanol, extracting with acetone and drying in sequence to obtain epoxidation-modified chitosan. In the present invention, the drying temperature is preferably 50 to 60° C., more preferably 55° C.; the present invention has no special limitation on the drying time, and drying to constant weight is sufficient.

[0156] In the present invention, the preparation method of ethylene glycol diglycidyl ether preferably comprises the following steps: mixing ethylene glycol, a catalyst and epichlorohydrin, performing a ring-opening addition reaction, and then performing a ring-closing reaction under alkaline conditions to obtain ethylene glycol diglycidyl ether. The reaction scheme is as follows:

[0157]

[0158] In the present invention, the ethylene glycol is preferably dried before use. Specifically, ethylene glycol is added to a reaction container, heated, air and moisture are excluded, and the temperature is lowered after drying to obtain dry ethylene glycol. In the present invention, the temperature after heating is preferably 90 to 100°C, and in specific embodiments, it can be 90°C, 92°C, 94°C, 95°C, 96°C, 98°C or 100°C. In the present invention, the drying time is preferably 30 to 35 minutes, and in specific embodiments, it can be 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes or 35 minutes. In the present invention, the temperature after cooling is preferably 50 to 85°C, and in specific embodiments, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C.

[0159] In the present invention, the catalyst preferably comprises boron trifluoride etherate. In the present invention, the mass of the catalyst preferably accounts for 0.4-0.6% of the mass of ethylene glycol, and in specific embodiments, it can be 0.4%, 0.45%, 0.5%, 0.55% or 0.6%.

[0160] In the present invention, the mixing preferably includes: adding ethylene glycol and a catalyst, and then dropping epichlorohydrin. In the present invention, the mixing temperature is preferably 50 to 85°C, and in specific embodiments can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C. The present invention has no particular limitation on the dropping speed of the epichlorohydrin, as long as the temperature of the reaction system is ensured to be 50 to 85°C.

[0161] In the present invention, the molar ratio of epichlorohydrin to ethylene glycol is 2.2-2.5:1, and in specific embodiments may be 2.2:1, 2.3:1, 2.4:1 or 2.5:1.

[0162] In the present invention, the temperature of the ring-opening addition reaction is preferably 50-85°C, and in specific embodiments it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C; the time of the ring-opening addition reaction is preferably 40-60 min, and in specific embodiments it can be 40 min, 45 min, 50 min, 55 min or 60 min; the time of the ring-opening addition reaction starts from the completion of the addition of epichlorohydrin.

[0163] In the present invention, the alkaline condition is preferably provided by an alkali metal hydroxide, and the alkali metal hydroxide preferably includes NaOH and / or KOH; the alkali metal hydroxide is preferably used in the form of an alkali metal hydroxide aqueous solution; the mass concentration of the alkali metal hydroxide aqueous solution is preferably 40-60%, and in a specific embodiment, it can be 40%, 45%, 50%, 55% or 60%; the alkali metal hydroxide aqueous solution is preferably added dropwise; in the present invention, the system after the ring-opening addition reaction is preferably cooled to 35-45°C (in a specific embodiment, it can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C), and then the alkali metal hydroxide aqueous solution is added dropwise. In the present invention, the molar ratio of epichlorohydrin to alkali metal hydroxide is preferably 1.5-2:1, and in a specific embodiment, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1.

[0164] In the present invention, the temperature of the ring-closing reaction is preferably 35-45°C, and in specific embodiments it can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C; the time of the ring-closing reaction is preferably 1-3h, and in specific embodiments it can be 1h, 1.5h, 2h, 2.5h or 3h; the time of the ring-closing reaction starts when the addition of the alkali metal hydroxide is completed.

[0165] After the ring-closure reaction is completed, the present invention preferably further comprises: filtering the reaction system obtained by the ring-closure reaction while hot, allowing the filtrate to stand for phase separation, and distilling the upper crude product under reduced pressure to obtain ethylene glycol diglycidyl ether. In the present invention, the purpose of the hot filtration is to remove the alkali metal chloride generated by the reaction. In the present invention, the purpose of the reduced pressure distillation is to remove residual water and reaction raw materials.

[0166] The preparation method of molybdenum dioxide nanoparticles is described in detail below.

[0167] In the present invention, the method for preparing molybdenum dioxide nanoparticles preferably comprises the following steps: mixing a glucose aqueous solution and a sodium molybdate aqueous solution, adjusting the pH value to 1 to 4, and performing a hydrothermal reaction to obtain molybdenum dioxide nanoparticles.

[0168] In the present invention, the concentration of the glucose aqueous solution is preferably 0.5-1 mol / L, and in specific embodiments, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L. In the present invention, the concentration of the sodium molybdate aqueous solution is preferably 0.5-1 mol / L, and in specific embodiments, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L. In the present invention, the volume ratio of the glucose aqueous solution to the sodium molybdate aqueous solution is preferably 2-4:1, and in specific embodiments, it can be 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0169] In the present invention, the mixing temperature is preferably 25-30° C.; the mixing time is preferably 10-15 min, and in specific embodiments it can be 10 min, 11 min, 12 min, 13 min, or 14 min, 15 min.

[0170] In the present invention, the acid used to adjust the pH value to 1-4 preferably includes HCl solution, and the concentration of the HCl solution is preferably 2-3 mol / L, more preferably 2.5 mol / L; in a specific embodiment, the pH value can be 1, 1.5, 2, 2.5, 3, 3.5 or 4.

[0171] In the present invention, the temperature of the hydrothermal reaction is preferably 180-220°C, and in specific embodiments it can be 180°C, 190°C, 200°C, 210°C or 220°C; the time of the hydrothermal reaction is preferably 18-25h, and in specific embodiments it can be 18h, 19h, 20h, 21h, 22h, 23h, 24h; 25h; the hydrothermal reaction preferably includes: placing the acidic mixed solution after adjusting the pH value to 1-4 in a reaction container, and placing the reaction container in a homogeneous hydrothermal reactor for hydrothermal reaction; the reaction container preferably includes a polytetrafluoroethylene-lined high-pressure hydrothermal reactor, and the volume filling ratio of the reaction container is preferably 40-70%, more preferably 50-60%.

[0172] After the hydrothermal reaction is completed, the present invention preferably further comprises: cooling the reaction system obtained by the hydrothermal reaction to room temperature, centrifuging, washing the obtained solid with water, washing with anhydrous ethanol and drying in sequence to obtain molybdenum dioxide nanoparticles (monoclinic phase). In the present invention, the number of times of water washing is preferably 2 to 3 times. In the present invention, the number of times of anhydrous ethanol washing is preferably 2 to 3 times. In the present invention, the drying temperature is preferably

[0173] Drying: putting the powdered material after centrifugation and washing into a temperature of 60-80°C, which may be 60°C, 65°C, 70°C, 75°C or 80°C in a specific embodiment; the drying time is preferably 10-15h, which may be 10h, 11h, 12h, 13h, 4h or 15h in a specific embodiment; the drying is preferably carried out in a vacuum drying oven.

[0174] The present invention provides a method for preparing the tissue-like natural collagen composite absorbable suture thread described in the above technical scheme, comprising the following steps: blending medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles, sodium alginate and water to obtain a spinning solution; spinning the spinning solution to obtain the tissue-like natural collagen composite absorbable suture thread.

[0175] In the present invention, the mass ratio of the tissue-like natural collagen, epoxidized modified chitosan and sodium alginate is the same as the mass ratio of the three in the tissue-like natural collagen composite absorbable suture, which will not be repeated here.

[0176] In the present invention, the concentration of medical grade tissue-like natural collagen in the spinning solution is preferably 12-25wt%. In specific embodiments, it can be 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt% or 25wt%.

[0177] In the present invention, the mixing preferably includes ultrasonic mixing. The present invention has no special limitation on the conditions of the mixing, as long as the molybdenum dioxide nanoparticles can be evenly dispersed and other raw materials can be evenly mixed.

[0178] After the spinning is completed, the present invention preferably further comprises: straightening the filaments obtained by the spinning and then solidifying them into a shape to obtain a tissue-like natural collagen composite absorbable suture.

[0179] In the present invention, the spinning process conditions preferably include: the coagulation bath is saturated sodium sulfate; the pressure is 0.05-0.2MPa, and in a specific embodiment it can be 0.05MPa, 0.1MPa, 0.15MPa or 0.2MPa; the spinning solution temperature is room temperature; the coagulation temperature is 25-35°C, and in a specific embodiment it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C; the winding speed is 8-15m / min, and in a specific embodiment it can be 8m / min, 9m / min, 10m / min, 11m / min, 12m / min, 13m / min, 14m / min or 15m / min; the spinning is preferably carried out in a wet spinning machine.

[0180] The present invention uses medical-grade tissue-like natural collagen, epoxy-modified chitosan, molybdenum dioxide nanoparticles and sodium alginate as raw materials, forms a spinning solution by blending, and then prepares a new type of medical antibacterial and scar-removing tissue-like natural collagen composite absorbable suture by spinning. The prepared tissue-like natural collagen composite absorbable suture not only retains the various advantages of medical-grade tissue-like natural collagen materials, but also can resist the corrosion of bile, urine and pancreatic juice due to the participation of chitosan. Compared with the existing natural absorbable sutures in terms of process cost, insufficient antigenicity, poor structural stability, short degradation cycle, poor fixation, etc., this new material has more advantages, has broad prospects, and is very meaningful.

[0181] The present invention also provides the application of the tissue-like natural collagen composite absorbable suture described in the above technical solution or the tissue-like natural collagen composite absorbable suture prepared by the preparation method described in the above technical solution in tissue engineering, regenerative medicine materials or implantable medical devices. In the tissue-like natural collagen composite absorbable suture provided by the present invention, the medical-grade tissue-like natural collagen has good biocompatibility, suitable biodegradability, good mechanical properties and excellent thermal stability and structural stability, low antigenicity and easy preservation, and can quickly and effectively stop bleeding, promote wound healing and repair, and is an ideal material for biomedical materials. It can fundamentally and thoroughly solve the problems of fast biodegradation and insufficient mechanical strength of collagen molecular hierarchical materials or gelatin materials. The present invention uses tissue-like natural collagen and also realizes the reuse of natural biological tissues. The present invention supplements and modifies the material by adding epoxidized modified chitosan, which has an inhibitory effect on the reproduction and growth of various bacteria and fungi, and can also promote skin regeneration and accelerate wound healing after suture. Molybdenum dioxide, as a metallic semiconductor, has good electrical conductivity. The present invention can not only improve the conductivity of the tissue-like natural collagen composite absorbable suture by adding molybdenum dioxide nanoparticles, but also further improve its wear resistance and anti-slip properties. In addition, the photothermal effect of molybdenum disulfide can also bring about obvious scar elimination effects. The sodium alginate added in the present invention is a linear polysaccharide with excellent biocompatibility, biodegradability, non-toxicity and low raw material cost. Chitosan and its derivatives have a broad spectrum of antibacterial effects, can inhibit the reproduction and growth of a variety of bacteria and fungi, and have the advantages of being non-toxic and having strong antibacterial properties. Wound dressings with added chitosan can prevent bacterial penetration, promote skin regeneration, and accelerate wound healing, coupled with its good biocompatibility, strength, flexibility and bioabsorbability. The tissue-like natural collagen composite absorbable suture provided by the present invention fully combines the advantageous functions of the components used, retains the excellent mechanical properties and biodegradability of the natural collagen composite material, has low antigenicity and excellent antibacterial properties, and also combines the photothermal effect of molybdenum disulfide, and has an obvious scar elimination effect; it also has good fixation, and can also resist the corrosion of bile, urine and pancreatic juice and promote cell growth.

[0182] To further illustrate the present invention, the tissue-like natural collagen composite absorbable suture provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0183] In the following examples, the unit ratio of mass fraction to volume fraction is kg:L, and the animal skin used is pig skin.

[0184] Example 1

[0185] Preparation of medical grade tissue-like natural collagen:

[0186] A) Animal skin pretreatment: The animal skin is placed in a rotary drum for repeated washing to remove dirt on the animal skin, and then soaked in water for 2 hours after washing, and then mechanically cut to remove subcutaneous fat, surface muscles, blood vessels, fascia tissue and other subcutaneous tissues on the animal skin as much as possible, and then cut into small pieces of 5.0 mm×5.0 mm, and then fully washed with physiological saline at room temperature and soaked for 15 hours to obtain pretreated animal skin;

[0187] B) Animal skin degreasing treatment: 10 parts by weight of the above-mentioned pretreated animal skin is put into a drum, 0.2 parts by weight of alkyl polyglycoside and water (the solid-liquid ratio of the pretreated animal skin to water is 1 kg:2 L) are added, and degreasing is carried out at 35° C. and a drum speed of 8 r / min for 3 hours. After degreasing, excess chemical reagents and grease are rinsed off with warm water at 35° C. to obtain defatted animal skin;

[0188] C) Animal skin dehairing treatment: the above-mentioned defatted animal skin is placed in water (the solid-liquid ratio of the pre-treated animal skin to water is 1kg:2L), 5 parts by weight of fatty alcohol polyoxyethylene ether and 4 parts by weight of ferrous sulfate are added to the water, the drum is rotated at 35°C and a drum speed of 8r / min for 2h, 0.2 parts by weight of triethanolamine is added, the drum is rotated for 20min, 0.4 parts by weight of sodium hydroxide is added, the drum is rotated for 20min, 0.6 parts by weight of hydrogen peroxide is added for rinsing for 4h, 0.5% sodium hydroxide solution is added for immersion for 5h, and then the drum is repeatedly rinsed with water to obtain dehaired animal skin;

[0189] D) Animal skin deswelling treatment: the depilated animal skin is put into a drum, water is added (the solid-liquid ratio of the pretreated animal skin to water is 1kg:1L), the temperature is controlled at 28°C, and 0.1% of the weight of the pretreated animal skin is added with sodium bisulfite, the drum is rotated at 35°C and the speed of the drum is 8r / min for 60min, and the end point pH value is controlled at 8; after the rotation is completed, 10 parts by volume of water and 4 parts by volume of formic acid are added to the same bath, the pH value is controlled to 4, and then 0.2% of the weight of the pretreated animal skin is added with acid lipase, the drum is rotated for 20min, and 0.3% of the weight of the pretreated animal skin is added with acid protease, the reaction is carried out at a constant temperature of 40°C for 5h, and finally rinsed repeatedly with ultrapure water to obtain deswelling animal skin;

[0190] E) Acid swelling treatment of animal skin: water is continuously added to the de-swollen animal skin (the solid-liquid ratio of the pre-treated animal skin to water is 1 kg:2 L), the pH value is adjusted to 3.0 with a mixed acid solution of 0.05-0.08 wt % formic acid solution and 0.08-0.12 wt % sulfuric acid solution (volume ratio = 1:2), the mixture is rotated at 35° C. and a drum speed of 8 r / min for 1 h, allowed to stand for 8 h, and repeatedly rinsed with water to obtain acid-swollen animal skin;

[0191] F) Preparation of tissue-like natural collagen: Take the above acid-swollen animal skin, put it and the material ball into a ball milling jar, make the ball-to-material ratio be 1:1.5, ball mill for 2 hours at a speed of 400r / min, centrifuge the slurry at 15000r / min for 15 minutes after the grinding, remove the supernatant, collect the slurry, adjust the pH of the slurry to 7.0 with 0.1mol / L sodium hydroxide aqueous solution, centrifuge at 15000r / min for 15 minutes, collect the precipitate, wash the precipitate with ultrapure water for 5 times, freeze-dry, sterilize with γ-rays generated by 60Co at a dose of 15KGy / h, and obtain medical-grade tissue-like natural collagen. Among them, the grinding bodies used in the ball mill are large balls with a particle size of 12-13mm and small balls with a particle size of 9-10mm, and the number ratio of large balls to small balls is 1:2.

[0192] Preparation of ethylene glycol diglycidyl ether epoxidized chitosan:

[0193] A) Preparation of ethylene glycol diglycidyl ether: Add ethylene glycol to a reaction flask, heat to 90° C. in a constant temperature water bath, remove air and moisture from the reaction flask, heat for 30 min, cool to 65° C., add boron trifluoride ether complex with a mass fraction of 0.4% ethylene glycol, dropwise add epichlorohydrin (the molar ratio of epichlorohydrin to ethylene glycol is 2.2:1), control the dropwise addition speed to keep the temperature constant, and continue the reaction for 40 min after the dropwise addition is completed;

[0194] The temperature was lowered to 40°C, and after the temperature was constant, a 40% NaOH aqueous solution (the molar ratio of epichlorohydrin to NaOH was 2:1) was added dropwise, and the reaction was continued for 2 hours after the addition was completed. After the reaction was complete, the sodium chloride generated by the reaction was removed by suction filtration while hot, and the filtrate was placed in a separatory funnel and allowed to stand for phase separation, and the saturated sodium chloride aqueous solution at the lower layer was filtered out, and the upper crude product was distilled under reduced pressure to remove the residual water and reactants to obtain ethylene glycol diglycidyl ether;

[0195] B) Epoxidized chitosan: 2 g of chitosan powder was suspended in 20 mL of distilled water, the temperature was raised to 95°C, 3 g of 2% ethylene glycol diglycidyl ether aqueous solution was added dropwise, and the reaction was continued with stirring for 3 h. The solid was filtered out, washed with water, ethanol, extracted with acetone, and dried at 50°C to constant weight to obtain epoxidized chitosan.

[0196] Preparation of monoclinic MoO2 nanoparticles:

[0197] The concentration of 0.5 mol / L C6H 12An O6·H2O aqueous solution and a Na2MoO4·2H2O aqueous solution with a concentration of 0.5 mol / L were mixed in a volume ratio of 2:1 and stirred at 30°C for 10 min; a 2 mol / L HCl solution was used to adjust the pH value of the mixed solution to 2, and the solution was poured into a polytetrafluoroethylene-lined high-pressure hydrothermal reactor with a volume filling ratio of 40%, and then the reactor was sealed and placed in a homogeneous hydrothermal reactor to react at 180°C for 18 h; after the reaction was completed, the solution was cooled to room temperature, the final reactant was centrifuged, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried in a 60°C vacuum drying oven for 12 h to obtain monoclinic molybdenum dioxide nanoparticles.

[0198] Preparation of tissue-like natural collagen composite absorbable suture:

[0199] Medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate are mixed in distilled water, stirred evenly, and ultrasonically dispersed the molybdenum dioxide nanoparticles to obtain a spinning solution, which is poured into a wet spinning machine to spin into filaments, straightened, and solidified to obtain a natural collagen composite absorbable suture with a circular cross-section; wherein the mass ratio of medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate is 10:1:0.1:1; the concentration of medical-grade tissue-like natural collagen in the spinning solution is 15wt%; the spinning process conditions are as follows: coagulation bath: saturated sodium sulfate; pressure: 0.1MPa; spinning solution temperature: room temperature; coagulation temperature: 25°C; winding speed: 10m / min.

[0200] Example 2

[0201] Preparation of medical grade tissue-like natural collagen:

[0202] A) Animal skin pretreatment: The animal skin is placed in a rotary drum for repeated washing to remove dirt on the animal skin, and then soaked in water for 2 hours after washing, and then mechanically cut to remove subcutaneous fat, surface muscles, blood vessels, fascia tissue and other subcutaneous tissues on the animal skin as much as possible, and then cut into small pieces of 5.0 mm×5.0 mm, and then fully washed with physiological saline at room temperature and soaked for 15 hours to obtain pretreated animal skin;

[0203] B) Animal skin degreasing treatment: 10 parts by weight of the above-mentioned pretreated animal skin is put into a rotary drum, 0.15 parts by weight of alkyl polyglycoside and water (the solid-liquid ratio of the pretreated animal skin to water is 1 kg:2 L) are added, and degreasing is carried out at 30° C. and a rotary drum speed of 10 r / min for 2.5 hours. After degreasing, excess chemical reagents and grease are rinsed off with warm water at 35° C. to obtain defatted animal skin;

[0204] C) Animal skin dehairing treatment: the above-mentioned defatted animal skin is placed in water (the solid-liquid ratio of the pre-treated animal skin to water is 1kg:1.5L), 5 parts by weight of fatty alcohol polyoxyethylene ether and 4 parts by weight of ferrous sulfate are added to the water, the drum is rotated at 30°C and a drum speed of 10r / min for 2h, 0.3 parts by weight of triethanolamine is added, the drum is rotated for 20min, 0.4 parts by weight of sodium hydroxide is added, the drum is rotated for 20min, 0.6 parts by weight of hydrogen peroxide is added for rinsing for 3h, 0.5% sodium hydroxide solution is added for immersion for 5h, and then the dehaired animal skin is repeatedly rinsed with water to obtain;

[0205] D) Animal skin deswelling treatment: the depilated animal skin is put into a drum, water is added (the solid-liquid ratio of the pretreated animal skin to water is 1kg:1L), the temperature is controlled at 28°C, and 0.1% of the weight of the pretreated animal skin is added with sodium bisulfite, the drum is rotated at 30°C and a speed of 10r / min for 50min, and the end point pH value is controlled at 8; after the rotation is completed, 10 parts by volume of water and 4 parts by volume of formic acid are added to the same bath, the pH value is controlled to be 4.5, and then 0.25% of the weight of the pretreated animal skin is added with acid lipase, the drum is rotated for 20min, and 0.25% of the weight of the pretreated animal skin is added with acid protease, the reaction is carried out at a constant temperature of 40°C for 5h, and finally rinsed repeatedly with ultrapure water to obtain deswelling animal skin;

[0206] E) Acid swelling treatment of animal skin: water is continuously added to the de-swollen animal skin (the solid-liquid ratio of the pre-treated animal skin to water is 1 kg:2 L), the pH value is adjusted to 3.0 with a mixed acid solution of 0.05-0.08 wt % formic acid solution and 0.08-0.12 wt % sulfuric acid solution (volume ratio = 1:2), the mixture is rotated at 30° C. and a drum speed of 10 r / min for 2 h, allowed to stand for 8 h, and repeatedly rinsed with water to obtain acid-swollen animal skin;

[0207] F) Preparation of tissue-like natural collagen: Take the above acid-swollen animal skin, put it and the material ball into a ball milling jar, make the ball-to-material ratio be 1:1.5, ball mill for 2 hours at a speed of 400r / min, centrifuge the slurry at 18000r / min for 15 minutes after the grinding, remove the supernatant, collect the slurry, adjust the pH of the slurry to 7.0 with 0.1mol / L sodium hydroxide aqueous solution, centrifuge at 18000r / min for 15 minutes, collect the precipitate, wash the precipitate with ultrapure water for 5 times, freeze-dry, sterilize with γ-rays produced by 60Co at a dose of 20KGy / h, and obtain medical-grade tissue-like natural collagen. Among them, the grinding bodies used in the ball mill are large balls with a particle size of 12-13mm and small balls with a particle size of 9-10mm, and the number ratio of large balls to small balls is 1:2.

[0208] Preparation of ethylene glycol diglycidyl ether epoxidized modified chitosan:

[0209] A) Preparation of ethylene glycol diglycidyl ether: Add ethylene glycol to a reaction flask, heat to 90° C. in a constant temperature water bath, remove air and moisture from the reaction flask, heat for 35 min, cool to 85° C., add boron trifluoride ether complex with a mass fraction of 0.6% ethylene glycol, dropwise add epichlorohydrin (the molar ratio of epichlorohydrin to ethylene glycol is 2.2:1), control the dropwise addition speed to keep the temperature constant, and continue the reaction for 40 min after the dropwise addition is completed;

[0210] The temperature was lowered to 40°C, and after the temperature was constant, a 40% NaOH aqueous solution (the molar ratio of epichlorohydrin to NaOH was 2:1) was added dropwise, and the reaction was continued for 3 hours after the addition was completed. After the reaction was complete, the sodium chloride generated by the reaction was removed by suction filtration while hot, and the filtrate was placed in a separatory funnel and allowed to stand for phase separation, and the saturated sodium chloride aqueous solution at the lower layer was filtered out, and the upper crude product was distilled under reduced pressure to remove the residual water and reactants to obtain ethylene glycol diglycidyl ether;

[0211] B) Epoxidized chitosan: 2 g of chitosan powder was suspended in 25 mL of distilled water, the temperature was raised to 95°C, 2.5 g of 5% by mass ethylene glycol diglycidyl ether aqueous solution was added dropwise, and the reaction was continued with stirring for 5 h. The solid was filtered out, washed with water, ethanol, extracted with acetone, and dried at 60°C to constant weight to obtain epoxidized chitosan.

[0212] Preparation of monoclinic MoO2 nanoparticles:

[0213] The concentration of 1 mol / L C6H 12 O6·H2O aqueous solution and Na2MoO4·2H2O aqueous solution with a concentration of 1 mol / L are mixed in a volume ratio of 4:1, and stirred at 30°C for 15 minutes; a 3 mol / L HCl solution is used to adjust the pH value of the mixed solution to 3, and the solution is poured into a polytetrafluoroethylene-lined high-pressure hydrothermal reactor with a volume filling ratio of 50%, and then the reactor is sealed and placed in a homogeneous hydrothermal reactor to react at 200°C for 20 hours; after the reaction is completed, the solution is cooled to room temperature, and the final reactant is centrifuged and washed with deionized water and anhydrous ethanol for 3 times respectively, and then placed in a vacuum drying oven at 80°C for 10 hours to obtain monoclinic molybdenum dioxide nanoparticles.

[0214] Preparation of tissue-like natural collagen composite absorbable suture:

[0215] Medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate are mixed in distilled water, stirred evenly, and ultrasonically dispersed the molybdenum dioxide nanoparticles to obtain a spinning solution, which is poured into a wet spinning machine to spin into filaments, straightened, and coagulated to obtain a natural collagen composite absorbable suture with a circular cross-section; wherein the mass ratio of medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate is 10:0.5:0.05:0.5; the concentration of medical-grade tissue-like natural collagen in the spinning solution is 18wt%; the spinning process conditions are as follows: coagulation bath: saturated sodium sulfate; pressure: 0.2MPa; spinning solution temperature: room temperature; coagulation temperature: 30°C; winding speed: 12m / min.

[0216] Example 3

[0217] Preparation of medical grade tissue-like natural collagen:

[0218] A) Animal skin pretreatment: The animal skin is placed in a rotary drum for repeated washing to remove dirt on the animal skin, and then soaked in water for 1 hour, and then mechanically cut to remove subcutaneous fat, surface muscles, blood vessels, fascia tissue and other subcutaneous tissues on the animal skin as much as possible, and then cut into small pieces of 10.0 mm × 10.0 mm, and then fully washed with physiological saline at room temperature and soaked for 18 hours to obtain pretreated animal skin;

[0219] B) Animal skin degreasing treatment: 10 parts by weight of the above-mentioned pretreated animal skin is put into a drum, 0.4 parts by weight of alkyl polyglycoside and water (the solid-liquid ratio of the pretreated animal skin to water is 1 kg:3 L) are added, and degreasing is performed at 30° C. and a drum speed of 10 r / min for 4 hours. After degreasing, excess chemical reagents and grease are rinsed off with 30° C. warm water to obtain defatted animal skin;

[0220] C) Animal skin dehairing treatment: the above-mentioned defatted animal skin is placed in water (the solid-liquid ratio of the pre-treated animal skin to water is 1kg:2L), 3 parts by weight of fatty alcohol polyoxyethylene ether and 6 parts by weight of ferrous sulfate are added to the water, the drum is rotated at 30°C and a drum speed of 10r / min for 2h, 0.45 parts by weight of triethanolamine is added, the drum is rotated for 20min, 0.8 parts by weight of sodium hydroxide is added, the drum is rotated for 10min, 0.8 parts by weight of hydrogen peroxide is added for rinsing for 3h, 0.5% sodium hydroxide solution is added for immersion for 5h, and then the drum is repeatedly rinsed with water to obtain dehaired animal skin;

[0221] D) Animal skin deswelling treatment: the depilated animal skin is put into a drum, water is added (the solid-liquid ratio of the pretreated animal skin to water is 1kg:8L), the temperature is controlled at 28°C, and 0.2% of the weight of the pretreated animal skin is added with sodium bisulfite, the drum is rotated at 30°C and a speed of 10r / min for 50min, and the end point pH value is controlled at 8; after the rotation is completed, 10 parts by volume of water and 3 parts by volume of formic acid are added to the same bath, the pH value is controlled to be 4.5, and then 0.15% of the weight of the pretreated animal skin is added with acid lipase, the drum is rotated for 20min, and 0.15% of the weight of the pretreated animal skin is added with acid protease, the reaction is carried out at a constant temperature of 40°C for 5h, and finally rinsed repeatedly with ultrapure water to obtain deswelling animal skin;

[0222] E) Acid swelling treatment of animal skin: water is continuously added to the de-swollen animal skin (the solid-liquid ratio of the pre-treated animal skin to water is 1 kg:2 L), the pH value is adjusted to 3.0 with a mixed acid solution of 0.05-0.08 wt % formic acid solution and 0.08-0.12 wt % sulfuric acid solution (volume ratio = 1:2), the mixture is rotated at 30° C. and a drum speed of 10 r / min for 2 h, allowed to stand for 8 h, and repeatedly rinsed with water to obtain acid-swollen animal skin;

[0223] F) Preparation of tissue-like natural collagen: Take the above acid-swollen animal skin, put it and the material ball into a ball mill, make the ball-to-material ratio 1:1.5, ball mill for 3 hours at a speed of 600r / min, centrifuge the slurry at 18000r / min for 15min after grinding, remove the supernatant, collect the slurry, adjust the pH of the slurry to 7.0 with 0.1mol / L sodium hydroxide aqueous solution, centrifuge at 18000r / min for 15min, collect the precipitate, wash the precipitate with ultrapure water for 5 times, freeze-dry, and sterilize with γ-rays generated by 60Co at a dose of 25KGy / h to obtain medical-grade tissue-like natural collagen. Among them, the grinding bodies used in the ball mill are large balls with a particle size of 12-13mm and small balls with a particle size of 9-10mm, and the number ratio of large balls to small balls is 1:2.

[0224] Preparation of ethylene glycol diglycidyl ether epoxidized chitosan:

[0225] A) Preparation of ethylene glycol diglycidyl ether: Add ethylene glycol to a reaction flask, heat to 90° C. in a constant temperature water bath, remove air and moisture from the reaction flask, heat for 30 min, cool to 65° C., add boron trifluoride ether complex with a mass fraction of 0.5% ethylene glycol, dropwise add epichlorohydrin (the molar ratio of epichlorohydrin to ethylene glycol is 2.2:1), control the dropwise addition speed to keep the temperature constant, and continue the reaction for 40 min after the dropwise addition is completed;

[0226] The temperature was lowered to 40°C, and after the temperature was constant, a 40% NaOH aqueous solution (the molar ratio of epichlorohydrin to NaOH was 2:1) was added dropwise, and the reaction was continued for 2 hours after the addition was completed. After the reaction was complete, the sodium chloride generated by the reaction was removed by suction filtration while hot, and the filtrate was placed in a separatory funnel and allowed to stand for phase separation, and the saturated sodium chloride aqueous solution at the lower layer was filtered out, and the upper crude product was distilled under reduced pressure to remove the residual water and reactants to obtain ethylene glycol diglycidyl ether;

[0227] B) Epoxidized chitosan: 2 g of chitosan powder was suspended in 25 mL of distilled water, the temperature was raised to 95°C, 3 g of 5% by mass ethylene glycol diglycidyl ether aqueous solution was added dropwise, and the reaction was continued with stirring for 4 h. The solid was filtered out, washed with water, ethanol, extracted with acetone, and dried at 60°C to constant weight to obtain epoxidized chitosan.

[0228] Preparation of monoclinic MoO2 nanoparticles:

[0229] The concentration of 1 mol / L C6H 12 O6·H2O aqueous solution and 1 mol / L Na2MoO4·2H2O aqueous solution were mixed in a volume ratio of 2:1 and stirred at 30°C for 15 min; 3 mol / L HCl solution was used to adjust the pH value of the mixed solution to 2, and the solution was poured into a polytetrafluoroethylene-lined high-pressure hydrothermal reactor with a volume filling ratio of 40%, and then the reactor was sealed and placed in a homogeneous hydrothermal reactor to react at 220°C for 18 h; after the reaction was completed, the solution was cooled to room temperature, the final reactant was centrifuged, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried in a vacuum drying oven at 80°C for 10 h to obtain monoclinic molybdenum dioxide nanoparticles.

[0230] Preparation of tissue-like natural collagen composite absorbable suture:

[0231] Medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate are mixed in distilled water, stirred evenly, and ultrasonically dispersed the molybdenum dioxide nanoparticles to obtain a spinning solution, which is poured into a wet spinning machine to spin into filaments, straightened, and coagulated to obtain a natural collagen composite absorbable suture with a circular cross-section; wherein the mass ratio of medical-grade tissue-like natural collagen, epoxidized modified chitosan, monoclinic molybdenum dioxide nanoparticles and sodium alginate is 10:0.25:0.05:0.25; the concentration of medical-grade tissue-like natural collagen in the spinning solution is 25wt%; the spinning process conditions are as follows: coagulation bath: saturated sodium sulfate; pressure: 0.2MPa; spinning solution temperature: room temperature; coagulation temperature: 30°C; winding speed: 15m / min.

[0232] Figure 1This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 1. Figure 2 This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 2. Figure 3 This is a physical picture of the tissue-like natural collagen composite absorbable suture prepared in Example 3. Figures 1 to 3 It can be seen that the tissue-like natural collagen composite absorbable suture thread prepared by the present invention is a multi-strand thread.

[0233] Example 4

[0234] A) Animal skin pretreatment: The animal skin is placed in a rotary drum for repeated washing to remove dirt on the animal skin, and then soaked in water for 90 minutes after washing, and then mechanically cut to remove subcutaneous fat, surface muscles, blood vessels, fascia tissue and other subcutaneous tissues on the animal skin as much as possible, and then cut into small pieces of 8.0 mm × 8.0 mm, and fully washed with physiological saline at room temperature and soaked for 13 hours to obtain pretreated animal skin;

[0235] B) Animal skin degreasing treatment: 10 parts by weight of the above-mentioned pretreated animal skin is put into a rotary drum, 0.3 parts by weight of alkyl polyglycoside and 20 parts by volume of deionized water are added, and degreasing is carried out at a constant temperature of 35° C. for 3 hours. After degreasing, the skin is repeatedly washed with warm water at 38° C. for 4 times to obtain defatted animal skin;

[0236] C) Animal skin dehairing treatment: the above-mentioned defatted animal skin is placed in water of equal weight, 5 parts by weight of fatty alcohol polyoxyethylene ether and 4 parts by weight of ferrous sulfate are added to the water, and after rotating in a drum for 2 hours, 0.2 parts by weight of triethanolamine is added, and after continuing to rotate for 15 minutes, 0.4 parts by weight of sodium hydroxide is added, and after rotating for 20 minutes, 0.7 parts by weight of hydrogen peroxide is added, and the skin is rotated for 3.5 hours. After the end, it is soaked in a sodium hydroxide solution with a mass fraction of 0.5% for 5 hours, and then repeatedly rinsed with ultrapure water for 4 times to obtain a dehaired animal skin;

[0237] D) Animal skin deswelling treatment: the depilated animal skin is put into a drum, 9 parts by volume of ultrapure water is added, the temperature is controlled at 30°C, and sodium bisulfite with a tare weight of 0.12% is added, and the drum is rotated for 55 minutes, and the end point pH value is controlled at about 8.3; after the rotation is completed, 10 parts by volume of deionized water and 3.5 parts by volume of formic acid are added to the same bath, and the pH value is controlled to be 4.2, and then 0.2% of acid lipase is added, and after rotating for 20 minutes, 0.2% of acid protease is added, and the reaction is carried out at a constant temperature of 40°C for 3 hours. Finally, it is repeatedly rinsed with ultrapure water for 4 times to obtain deswelling animal skin;

[0238] E) Acid swelling treatment of animal skin: 15 parts by volume of ultrapure water was further added to the de-swollen animal skin, and the pH value was adjusted to 2.9 with a mixed acid solution of 0.05-0.08wt% formic acid solution and 0.08-0.12wt% sulfuric acid solution (volume ratio = 1:2), stirred for 0.8h, and then rinsed repeatedly with ultrapure water for 4 times after standing for 7h to obtain acid-swollen animal skin;

[0239] F) Preparation of tissue-like natural collagen: Take the above acid-swollen animal skin, put it and the material ball into a ball milling jar, make the ball-to-material ratio 1:3, ball mill for 120min at a speed of 400r / min, centrifuge the slurry at 16000r / min for 13min after grinding, remove the supernatant, collect the slurry, adjust the pH of the slurry to 7.2 with sodium carbonate, centrifuge at 16000r / min for 13min, collect the precipitate, wash the precipitate with ultrapure water 4 times, finally freeze-dry, sterilize with γ-rays produced by 18KGy / h60Co, shape and package, and obtain medical-grade tissue-like natural collagen. Among them, the grinding bodies used in the ball mill are large balls with a particle size of 12-13mm and small balls with a particle size of 9-10mm, and the number ratio of large balls to small balls is 1:2. The drum speed in this embodiment is 10r / min.

[0240] Comparative Example 1

[0241] Antigen-free collagen aggregates prepared in Example 2 of Chinese Patent CN104107456A.

[0242] Comparative Example 1 uses acetone and supercritical fluid for degreasing. Acetone has certain toxicity, and the industrialization of supercritical fluid devices is relatively complicated. Under the condition of achieving the same degreasing effect, the present invention uses alkyl polyglycosides with better biocompatibility, and the equipment also uses conventional leather equipment drums, which are more suitable for industrial applications. The preparation method provided by the present invention adds a depilatory process relative to Comparative Example 1. This process can further remove non-collagen components in the skin such as miscellaneous proteins and fiber stroma while removing hair, further loosen the collagen fibers in the skin, facilitate the subsequent extraction of natural collagen, and improve the extraction rate of natural collagen. Comparative Example 1 uses a homogenizer beating process, and inevitably a large number of small particles of leather pieces are retained because the beating process cannot ensure complete homogenization, affecting subsequent applications; while the present invention uses a ball milling process that is more in line with industrial production. The preparation cycle under this process is shorter, the extraction rate of natural collagen is higher, and the ball milling process used is more uniform in sample preparation, and the quality is more controllable.

[0243] Test Example 1

[0244] Performance measurement method of tissue-like natural collagen composite absorbable suture prepared in Examples 1 to 3 and performance comparison with traditional absorbable sutures (catgut sutures, synthetic fiber sutures)

[0245] (1) Determination of linear density, breaking strength and breaking elongation

[0246] The tensile strength and elongation at break of a single fiber were measured using a domestic YG001A fiber electronic strength tester. The initial fiber length was 20 mm and the tensile rate was 10 mm / min. Each fiber sample was measured 10 times and the average value was taken. When measuring the linear density of the fiber, the fiber was first cut with a Y171 fiber cutter, and then the JN-B precision torsion balance was used to measure the mass of 50 fibers with a length of 20 mm. The results are shown in Table 1.

[0247] Table 1 Test results of linear density, breaking strength and breaking elongation of suture thread

[0248] sample Linear density (dtex) Breaking strength (cN / dtex) Elongation at break (%) Catgut suture 4.2 0.54 25.06 Collagen suture 4.0 0.55 13.25 Example 1 6.9 0.88 18.56 Example 2 6.6 0.85 14.65 Example 3 7.2 0.93 16.57

[0249] It can be seen from Table 1 that the tissue-like natural collagen composite absorbable suture prepared by the present invention has more advantages in material strength than traditional collagen and goat intestine absorbable sutures.

[0250] (2) Determination of in vitro degradability

[0251] Preparation of Hanks degradation solution: Dissolve 160g NaCl, 8g KCl, 2g MgSO4·7H2O and 2g MgCl2·6H2O in 100mL double distilled water to obtain solution A, dissolve 2.8g CaCl2 in 100mL double distilled water to obtain solution B, mix solution A and solution B, add double distilled water to 1000mL, and then add 2mL chloroform for preservation to obtain stock solution A, which is stored at 4°C. Dissolve 3.04g Na2HPO4·12H2O, 1.20g KH2PO4, 20.0g glucose and 100mL phenol red solution with a concentration of 4.0g / L in 800mL double distilled water to obtain solution C, add double distilled water to 1000mL, and then add 2ml chloroform for preservation to obtain stock solution B, which is stored at 4°C. Stock solution A, stock solution B and double distilled water were mixed in a volume ratio of 1:1:18, and sterilized at 115°C for 10 min to obtain Hanks degradation solution.

[0252] Method: Take 0.02g of each suture sample, place it in a test tube, add 10mL of Hanks degradation solution, soak the suture sample completely, then seal the test tube and place it in a 37℃±1℃ water bath, change the Hanks degradation solution once a week. Take samples on the 7th, 14th and 21st day, clean them with distilled water, vacuum dry them for 5h, and measure the residual fiber mass. Calculate the degradation rate (i.e., the percentage of mass loss), and the results are shown in Table 2.

[0253] Table 2 Suture degradation rate test results

[0254] sample Collagen suture Catgut suture Example 1 Example 2 Example 3 7-day degradation rate / % 28.9 15.6 17.8 16.9 17.5 14-day degradation rate / % 36.4 23.3 25.4 23.8 24.6 28 days degradation rate / % 38.5 27.4 29.6 28.4 29.4

[0255] As can be seen from Table 2, the tissue-like natural collagen composite absorbable suture prepared by the present invention has more advantages in biodegradability than traditional collagen and goat intestine absorbable sutures.

[0256] (3) Determination of antibacterial activity (oscillation method)

[0257] Referring to the standard GB / T20944.3, the experimental bacteria were standard strains of Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), and the in vitro antibacterial properties of the absorbable suture prepared in the embodiment were quantitatively evaluated. The specific experimental steps are as follows:

[0258] (1) Prepare Luria-Bertani (LB) liquid medium according to GB / T20944.3

[0259] (2) Prepare Luria-Bertani (LB) solid culture medium according to GB / T20944.3

[0260] (3) Prepare bacterial suspension according to GB / T20944.3, and use culture tubes containing only S. aureus and E. coli as blank controls.

[0261] (4) Weigh 100 mg of the tissue-like natural collagen composite absorbable suture prepared in the example, the goat intestine suture as a comparison sample, and the collagen suture, respectively, put them into a 50 mL centrifuge tube, and sterilize them under ultraviolet light for 30 min for later use.

[0262] (5) Dilute the bacterial solution to 10 using sterile phosphate buffered saline (PBS) solution. 6 CFU / mL, 20mL LB liquid culture medium and 600μL diluted bacterial solution were added to the centrifuge tubes respectively, and no sample was added to the blank control group. The blank control group and the centrifuge tubes containing several groups of different absorbable suture samples were shaken and cultured for 18h using a constant temperature oscillator (ambient temperature: 37℃). Then the bacterial solution was diluted with sterile PBS solution (10 times in a row), and 1mL of the dilution was carefully applied on the LB solid culture medium. After the operation was completed, it was placed in a constant temperature incubator (ambient temperature: 37℃) for 18h and the number of colonies was recorded. The number of colonies was calculated according to the counting principle of the national standard GB4789.2, and the bacterial solution concentration and antibacterial rate were calculated according to the standard GB / T20944.3. The results are shown in Table 3.

[0263] Table 3 Antibacterial performance test results of sutures

[0264] sample Colony count Dilution multiple Bacterial concentration (CFU / mL) Antibacterial rate Blank control 109 107 <![CDATA[1.09×10 8 ]]> / Catgut suture 119 107 <![CDATA[1.05×10 8 ]]> 0 Collagen suture 112 107 <![CDATA[6.1×10 7 ]]> 0 Example 1 90 105 <![CDATA[9.9x10 5 ]]> 99.10% Example 2 72 104 <![CDATA[8.45x10 4 ]]> 99.45% Example 3 88 106 <![CDATA[1.21x10 6 ]]> 98.87%

[0265] As shown in Table 3, the tissue-like natural collagen composite absorbable suture prepared by the present invention has more advantages in antibacterial property than the traditional collagen and goat intestine absorbable sutures.

[0266] (4)2. Wound healing speed and scar elimination effect

[0267] The tissue-like natural collagen composite absorbable suture prepared in the embodiment is applied to the emergency animal model treatment of cutting trauma. New Zealand white rabbits are selected, the wound site is set at the back, the wound length is about 10cm, the wound depth is <20mm, and collagen sutures are used to suture tissue incisions as a control group. The healing of the wound after the animals are treated with sutures is observed, and the degree of wound healing is used as the evaluation standard. In the observation group, both the short-term healing (3 days) and long-term healing effects (21 days) are good, and the healing rate is 100%. The standard for good short-term healing effect: no bleeding and exudation of the incision, no tenderness of the incision after 72h. The standard for good long-term healing effect: no induration around the incision, no scar on the incision, and some are even hidden. In the control group, 90% of the work period healed, 10% had the phenomenon of collagen suture line breaking, and some animals had induration at the incision. It can be seen that the absorbable suture prepared by this patent is more advantageous in promoting wound healing than traditional absorbable sutures. The observation group and the experimental group were observed 3 months after suturing, and the Vancouver Scar Scale was used to evaluate and compare the scar formation of the wound surface. The scale includes 4 dimensions, with a score of 0 to 15 points, 0 points for no scar, 1 to 5 points for mild scar, 6 to 10 points for moderate scar, and 11 to 15 points for severe scar. Among them, in the observation group, 24 rabbits had no scars, 16 had mild scars, and the average score was 1.2 points; in the control group, 12 rabbits had no scars, 27 had mild scars, and 1 had moderate scars, with an average score of 2.175 points. It can be seen that the new medical absorbable suture invented by this patent also has a promoting effect on the elimination of scars in wounds.

[0268] Test Example 2

[0269] Performance testing of collagen materials (medical-grade tissue-like natural collagen prepared in Example 4, antigen-free collagen aggregates prepared in Comparative Example 1, and commercially available molecular-grade collagen).

[0270] (1) The results of collagen extraction rate and impurity protein content of collagen materials are shown in Table 4.

[0271] Table 4 Collagen extraction rate and impurity protein content results of collagen materials

[0272] collagen Collagen extraction rate Miscellaneous protein content Comparative Example 1 75% 0.8wt% Example 4 92% 0.4wt%

[0273] It can be seen from Table 4 that, compared with Comparative Example 1, the collagen extraction rate of the medical-grade tissue-like natural collagen prepared by the present invention is significantly improved, and the impurity protein content is significantly reduced.

[0274] (2) The weight loss of collagen materials in different temperature ranges is shown in Table 5.

[0275] Table 5 Weight loss of collagen materials at different temperature ranges

[0276]

[0277] It can be seen from Table 5 that, compared with Comparative Example 1 and collagen, the medical-grade tissue-like natural collagen prepared by the present invention has a lower weight loss rate in the temperature range of 50 to 800° C. and better thermal stability and structural stability.

[0278] (3) 30-day degradation rate test method: Degradation in collagenase solution, the specific operation is as follows: bacterial type I collagenase is dissolved in PBS buffer to prepare a type I collagenase degradation solution (1U / mL) with a concentration of 2mL / mg. The samples are freeze-dried and immersed in the degradation solution for 30 days. After that, the degradation experiment is carried out in a 37°C constant temperature biochemical incubator.

[0279] Tensile strength test method: Pour the collagen sample into a polytetrafluoroethylene mold to cast it into a film, and then use a universal tensile testing machine to test the tensile strength of the sample.

[0280] Hemostasis time test method: rabbit ear central artery hemostasis model.

[0281] The hemostatic effect, degradation rate and tensile strength of the collagen material are shown in Table 6.

[0282] Table 6 Hemostasis, degradation and tensile strength results of collagen materials

[0283] sample Bleeding time 30-day degradation rate Tensile Strength Example 4 68s 68% 3.2MPa Comparative Example 1 116s 89% 2.4MPa collagen 182s 100% 0.9MPa

[0284] It can be seen from Table 6 that, compared with Comparative Example 1 and collagen, the medical-grade tissue-like natural collagen prepared by the present invention has a shorter hemostatic time and a better hemostatic effect; a lower 30-day degradation rate and a slower degradation speed; and a higher tensile strength.

[0285] (4) MTT assay

[0286] Experimental method: Use culture medium containing 10% fibroblasts to prepare a single cell suspension, inoculate 1000-10000 cells per well into a 96-well plate, and the volume of each well is 200 μL. Under standard culture conditions, maintain cell culture for 3-5 days. After the culture period, add 10 μL of MTT solution to each well and continue incubation for 4 hours. Terminate the culture and carefully discard the culture supernatant in the well. For suspended cells, centrifuge and then discard the culture supernatant in the well. After that, add 100 μL of dimethyl sulfoxide (DMSO) to each well and shake for 10 minutes to fully dissolve the crystals. Finally, select a wavelength of 490 nm, measure the light absorption value of each well on an enzyme-linked immunosorbent monitor, and record the results. Draw a cell growth curve with time as the horizontal axis and absorbance as the vertical axis to evaluate the growth of cells.

[0287] Figure 4 From the MTT test results of collagen, the antigen-free collagen aggregates prepared in Comparative Example 1, and the medical-grade tissue-like natural collagen prepared in Example 4, it can be seen that the medical-grade tissue-like natural collagen prepared by the present invention provides a more suitable growth environment for cells, shows significant advantages in promoting the proliferation and growth of fibroblasts, and provides a more ideal growth microenvironment for cells.

[0288] (5) 24h scratch test

[0289] Experimental method: Use a marker pen to draw horizontal lines on the back of a six-well plate with a ruler as a reference for subsequent experiments. Inoculate 3×10 5 cells, with a total volume of 2 mL per well; after culturing the cells for 24 hours, use a 200 μL pipette tip to scratch the cell layer along the pre-marked line to form a "wound"; after the scratching is completed, the culture supernatant is aspirated, and the cells are washed 2 to 3 times with PBS to remove the scratched cells; the old culture medium is discarded, and the medium containing drugs or serum-free medium is added according to the experimental grouping; the cells are cultured in a 37°C, 5% CO2 incubator. The cells are taken out at predetermined time points such as 0h and 24h, and the changes in the width of the scratches at the same position are observed and recorded under a microscope, and photos are taken to observe the changes in cell migration.

[0290] Figure 5 This is the 24h scratch result of collagen. Figure 6 This is the 24h scratch result of the antigen-free collagen aggregate prepared in Comparative Example 1. Figure 7 This is the 24h scratch result of the medical-grade natural tissue collagen prepared in Example 4. Figure 5 to Figure 7 It can be seen that compared with collagen and the antigen-free collagen aggregate prepared in Comparative Example 1, the medical-grade tissue-like natural collagen prepared by the present invention can better promote cell growth and proliferation, and is more conducive to wound tissue regeneration and reducing scar formation.

[0291] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A tissue-like natural collagen composite absorbable suture, comprising medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles, and sodium alginate.

2. The tissue-like natural collagen composite absorbable suture according to claim 1, characterized in that: The mass ratio of the tissue-like natural collagen to the epoxidized modified chitosan is 10:0.25-1.5; The mass ratio of the medical-grade tissue-like natural collagen to the molybdenum dioxide nanoparticles is 10:0.01-0.1; The mass ratio of the medical-grade tissue-like natural collagen to sodium alginate is 10:0.25-1.5; The molybdenum dioxide nanoparticles include monoclinic molybdenum dioxide nanoparticles.

3. The tissue-like natural collagen composite absorbable suture according to claim 1 or 2, characterized in that: The method for preparing the medical-grade tissue-like natural collagen comprises the following steps: (1) removing subcutaneous tissue of animal skin and soaking in physiological saline to obtain pretreated animal skin; (2) degreasing the pretreated animal hide to obtain a defatted animal hide; (3) dehairing the defatted animal hide to obtain a dehaired animal hide; (4) subjecting the depilated animal skin to a deswelling treatment to obtain a deswelling animal skin; (5) subjecting the de-swollen animal skin to an acid swelling treatment to obtain an acid swollen animal skin; (6) The acid-swollen animal skin is crushed, the pH value is adjusted to 7-7.4, the solid-liquid separation is performed to obtain a solid component, and the solid component is washed with water and then dried to obtain medical-grade tissue-like natural collagen.

4. The preparation method according to claim 3, characterized in that: In step (2), the degreasing treatment comprises: adding a degreasing agent and water to the pretreated animal skin to perform a degreasing treatment; The mass ratio of the pretreated animal skin to the degreasing agent is 1:0.01-0.04; The degreasing agent includes one or more of alkyl polyglycosides, peregrin, washing powder, sodium lauryl sulfate and fatty alcohol polyoxyethylene ether; The mass volume ratio of the pretreated animal skin to water is 1kg:1.5-3L; The degreasing treatment is performed at a temperature of 30 to 37°C for 2 to 5 hours; The degreasing treatment further includes water washing; In step (3), the depilatory treatment includes: adding the defatted animal skin, water, polyoxyethylene ether and ferrous salt to perform a first depilatory treatment, adding alcohol amine to perform a second depilatory treatment, adding an alkaline agent to perform a third depilatory treatment, adding an oxidant to perform a fourth depilatory treatment, and adding a dilute alkaline agent aqueous solution to perform a fifth depilatory treatment; The mass volume ratio of the defatted animal skin and water is 1kg:1-2L; The polyoxyethylene ether includes fatty alcohol polyoxyethylene ether and / or nonylphenol polyoxyethylene ether; the mass ratio of the pretreated animal skin to the polyoxyethylene ether is 1:0.3-0.6; The ferrous salt includes ferrous sulfate and / or ammonium ferrous sulfate; the mass ratio of the pretreated animal skin to the ferrous salt is 1:0.3-0.6; The first hair removal treatment lasts for 90 to 150 minutes; The alcoholamine includes one or more of triethanolamine, monoethanolamine and diethanolamine; the mass ratio of the pretreated animal skin to the alcoholamine is 1:0.01-0.03; The second hair removal treatment lasts for 10 to 20 minutes; The alkaline reagent includes alkali metal hydroxide and / or alkali metal carbonate; the mass ratio of the pretreated animal skin to the alkaline reagent is 1:0.035-0.045; The third hair removal treatment lasts for 15 to 25 minutes; The oxidant includes one or more of hydrogen peroxide, sodium perborate and sodium percarbonate; the mass ratio of the pretreated animal skin to the oxidant is 1:0.06-0.08; The fourth hair removal treatment lasts for 3 to 4 hours; The alkaline agent in the dilute alkaline agent aqueous solution includes alkali metal hydroxide and / or alkali metal carbonate; the mass fraction of the dilute alkaline agent aqueous solution is 0.3-0.8%; the time of the fifth depilatory treatment is 4-6 hours; The depilatory treatment also includes washing with water; In step (4), the deswelling treatment comprises: adding a first portion of water and an inorganic salt to the dehaired animal skin for a first deswelling treatment, adding a second portion of water, adjusting the pH value to 4 to 4.5, adding acid lipase for a second deswelling treatment, and adding acid protease for a third deswelling treatment; The mass volume ratio of the pretreated animal skin to the first portion of water is 1 kg: 0.8 to 1 L; The inorganic salt includes one or more of sodium bisulfite, ammonium sulfate, ammonium chloride and ammonium acetate; the mass of the inorganic salt accounts for 0.05-0.2% of the mass of the pretreated animal skin; The temperature of the first deswelling treatment is 28-35°C, the time is 50-60 minutes, and the end point pH value is 8-8.5; The mass volume ratio of the pretreated animal skin to the second part of water is 1 kg: 1 L to 4 L; The mass of the acid lipase accounts for 0.1-0.3% of the mass of the pretreated animal skin; the enzyme activity of the acid lipase is 50,000-60,000 units / g; The second deswelling treatment is performed at a temperature of 28 to 35°C for 15 to 20 minutes; The mass of the acidic protease accounts for 0.1-0.3% of the mass of the pretreated animal skin; the enzyme activity of the acidic protease is 80,000-100,000 units / g; The temperature of the third deswelling treatment is 38-42°C and the time is 2-5 hours; The deswelling treatment further includes washing with water; In step (5), the acid swelling treatment comprises: adding water to the de-swollen animal skin, adjusting the pH value to 2.8 to 3.0, stirring the acid swelling treatment and then standing the acid swelling treatment; The mass volume ratio of the pretreated animal skin to water is 1 kg: 1 to 2 L; The stirring acid swelling treatment time is 30 to 60 minutes; The time of the static acid swelling treatment is 6 to 8 hours; The acid swelling treatment further includes water washing. In step (6), the pulverization includes ball milling, the ball-to-material ratio of the ball milling is 1:1-5, the rotation speed is 200-600 r / min, and the time is 1-3 h; The drying comprises freeze drying; The drying process also includes disinfection and sterilization.

5. The tissue-like natural collagen composite absorbable suture according to claim 1 or 2, characterized in that: The epoxidized modified chitosan includes epoxidized modified chitosan obtained by epoxidizing chitosan with ethylene glycol diglycidyl ether.

6. The tissue-like natural collagen composite absorbable suture according to claim 5, characterized in that: The preparation method of the epoxidized modified chitosan comprises the following steps: Chitosan, ethylene glycol diglycidyl ether and water are mixed and epoxidized to obtain epoxidized modified chitosan.

7. The method for preparing the tissue-like natural collagen composite absorbable suture according to claims 1 to 6 comprises the following steps: Medical-grade tissue-like natural collagen, epoxidized modified chitosan, molybdenum dioxide nanoparticles, sodium alginate and water are mixed to obtain a spinning solution; The spinning solution is spun to obtain a tissue-like natural collagen composite absorbable suture thread.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the tissue-like natural collagen to the epoxidized modified chitosan is 10:0.25-1.5; The mass ratio of the medical-grade tissue-like natural collagen to the molybdenum dioxide nanoparticles is 10:0.01-0.1; The mass ratio of the medical-grade tissue-like natural collagen to sodium alginate is 10:0.25-1.5; The concentration of medical grade natural collagen in the spinning solution is 12-25wt%.

9. The preparation method according to claim 7 or 8, characterized in that: The spinning process conditions include: the coagulation bath is saturated sodium sulfate; the pressure is 0.05-0.2 MPa; the spinning solution temperature is room temperature; the coagulation temperature is 25-35° C.; and the winding speed is 8-15 m / min.

10. Use of the tissue-like natural collagen composite absorbable suture thread according to any one of claims 1 to 6 or the tissue-like natural collagen composite absorbable suture thread prepared by the preparation method according to any one of claims 7 to 9 in tissue engineering, regenerative medicine materials or implantable medical devices.

Citation Information

Patent Citations

  • High-purity natural collagenous fiber and preparation method thereof

    CN104189944A

  • Preparation method of antibacterial suture line

    CN108653796A

  • Metal oxide composite material and preparation method and application thereof

    CN115624966A

  • Glycerol triglycidyl ether modified oligomeric chitosan-based organic chrome-free tanning agent as well as preparation method and application of glycerol triglycidyl ether modified oligomeric chitosan-based organic chrome-free tanning agent

    CN116083659A

  • Porcine achilles tendon collagen absorbable antibacterial surgical suture and preparation method thereof

    CN117298323A